Analisis Implementasi Model Problem Based Learning dan Hubungannya Dengan Sikap Kreatif Siswa Kelas X Pada Materi Ikatan Kimia - Siti Nurjannah (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of the study: This study aims to analyze the Implementation of the Problem Based Learning Model and its Correlation to the Creative Attitudes of Students in the Chemical Bonding Material for Class X SMA Negeri 5 Tanjung Jabung Timur. Methodology: This research is a correlational descriptive with a purposive sampling technique. Data were collected using an instrument in the form of an observation sheet on the implementation of PBL mode and students' creative attitudes. The data was obtained in the form of quantitative data and qualitative data. Quantitative data were tested by regression to see the significance of the effect of implementing the problem-based learning model on students' creative attitudes. While the qualitative data obtained were analyzed using the analysis of Miles and Huberman. Main Findings: The analysis results show that the implementation of the PBL model by teachers and students is included in the good category. The correlation coefficient obtained is 0.707, meaning that the relationship between the implementation of the PBL model and students' creative attitudes has a strong relationship level. The results of the t-test indicate that tcount > ttable is 5,295>2,048, which means that the implementation of the PBL model affects students' creative attitudes. Novelty/Originality of this study: Thus, it can be concluded that there is a relationship between the implementation of the PBL model and the creative attitude of class X students of SMA Negeri 5 Tanjung Jabung Timur on chemical bonding.